MEASURING PERCENTAGE OF BIODIESEL IN DIESEL FUEL USING ULTRASONIC WAVE - SYAHNARIZA NAN BARENO (NIM : 13311034), FADYA
Biodiesel is one of the altenative diessel fuel. Biodiesel has some advantages and disadvantages. To overcome these disadvantages, biodiesel have to react to fossil diesel first. The percentage of biodiesel in diesel fuel is quite important as the indicator for quality of diesel fuel in applications. To estimate the percentage of biodiesel in diesel fuel accurately, precisely, fast, and user friendly, in this study the ultrasonic based instrument is proposed. To perform ultrasonic measurement, two types of transducers placement were used. First, the distance between transmitter and receiver which had frequency in 2.25 MHz were 13,23 cm. Second, the distance between transmitter and receiver which had frequency in 2 MHz were 1.13 cm. The result of both designed ultrasonic measurement were time of flight ultrasonic wave. The longest distance obtained better result than the shortest distance. The longest distance obtained the highest accuration and precision, so these result were used as the learning data for neural network. Neural network were used as the data interpretation. The input of neural network was not only the time of flight, but also colour of the sample and kinematic viscocity of biodiesel at room temperature. The outcome of data interpretation was using three types of neural network (NN 1, NN 2, NN 3) then compared with linear regression approximation. Average failure for linear regression was 24.51%. The average failure for NN 1 and NN 3 were 14,13% and 14,58%. Among three types of neural network, NN 2 proved the best performance which had the lowest average failure, 12,66%.